Volleyball as a means to develop speed endurance in girls aged 16-18 - Iryna Kryventsova; Yevheniia Strelnykova; Roman Boichuk; Krzysztof Wnorowski (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. There is an increasing interest in using volleyball as a means of physical activity among high school students and a need to assess its impact on speed endurance. The purpose of the study is to identify effective volleyball means for developing speed endurance in high school students in the context of distance and in-person learning.